Long Non-Coding RNAs: Role in Testicular Cancers - Bresesti, Chiara; Vezzoli, Valeria; Cangiano, Biagio; Bonomi, Marco (Frontiers in Oncology, 2021)
In the last few years lncRNAs have gained increasing attention among the scientific community, thanks to the discovery of their implication in many physio-pathological processes. In particular, their contribution to tumor initiation, progression and response to treatment has attracted the interest of experts in the oncologic field for their potential clinical application. Among the tumors in which lncRNAs role is emerging we can find testicular tumors. Said malignancies already have very effective treatments, which although lead to the development of quite serious treatment-related conditions, such as secondary tumors, infertility and cardiovascular diseases. It is therefore important to study the impact of lncRNAs in the tumorigenesis of testicular cancer in order to learn how to exploit them in a clinical setting and to substitute more toxic treatments. Eventually, the use of lncRNAs as biomarkers, drug targets or therapeutics for testicular cancer may represent a valid alternative to that of conventional tools, leading to a better management of this malignancy, maybe also those with a poor prognosis, and its related conditions.